2006
DOI: 10.1007/s10530-006-9021-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of invasive earthworms on indigenous fauna in ecosystems previously uninhabited by earthworms

Abstract: 2006 be contributing to declines in vertebrate fauna such as terrestrial salamanders. Preliminary evidence also suggests the potential for earthworm invasions to interact with other factors such as soil pollution, to negatively affect vertebrate populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 70 publications
3
49
1
Order By: Relevance
“…focused on the ecosystem-level effects of earthworms via effects on nutrient cycling and vegetation (reviewed in Hendrix et al 2006), many earthworm species also make burrows that can provide new habitat for other organisms (e.g., microinvertebrates; reviewed in Migge-Kleian et al 2006). Use of earthworm burrows by common vertebrates such as salamanders has not yet been studied, but such an interaction between earthworms and salamanders could be important to aboveground faunal communities (sensu van der Putten et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…focused on the ecosystem-level effects of earthworms via effects on nutrient cycling and vegetation (reviewed in Hendrix et al 2006), many earthworm species also make burrows that can provide new habitat for other organisms (e.g., microinvertebrates; reviewed in Migge-Kleian et al 2006). Use of earthworm burrows by common vertebrates such as salamanders has not yet been studied, but such an interaction between earthworms and salamanders could be important to aboveground faunal communities (sensu van der Putten et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, facilitation processes, such as those provided by wood-boring beetles, allow other invertebrates to colonise fallen trees and hence to find shelter, food, and places for egg laying (Zhuo et al, 2006). Predation and competition for space and resources are the most commonly reported negative interactions occurring among soil biota, but also habitat disturbances due to, for example, burrowing and mixing by earthworms (Migge-Kleaian et al, 2006). In many other cases, biotic interactions can be simultaneously positive and negative.…”
Section: Soil Biodiversity Abundance and Distribution In The Soils mentioning
confidence: 99%
“…For example, the outcome of a laboratory experiment, in which earthworms were involved, included negative interactions such as a reduction in population numbers of collembolans, but also positive effects such as an increase in the diversity and evenness of this mesofaunal community (Mudrák et al, 2012). However, positive and/or negative effects are often transient and hence, only one of them determines the overall response in the long-term (Migge-Kleaian et al, 2006).…”
Section: Soil Biodiversity Abundance and Distribution In The Soils mentioning
confidence: 99%
“…Conversely, other studies have reported that the incorporation of organic material into mineral soil by exotic earthworms increases soil microbial biomass (Burtelow et al 1998;Bohlen et al 1999;Li et al 2002;Groffman et al 2004). Modification of the soil matrix coupled with the feeding activity of earthworms can increase litter decomposition rates (Suárez et al 2006;Holdsworth et al 2008), change the availability and retention of soil carbon, nitrogen, and phosphorus (Bohlen et al 2004a,b;Suárez et al 2004;Hale et al 2005b;Szlavecz et al 2006), alter the size and structure of soil microbial (McLean and Parkinson 2000;Groffman et al 2004;McLean et al 2006;Dempsey et al 2011) and soil microfauna communities (McLean and Parkinson 1998;Migge-Kleian et al 2006), affect the abundance of arbuscular mycorrhizal fungi populations (Lawrence et al 2003), and change the distribution of plant fine roots . Depletion of the organic horizons and leaf litter layers by exotic earthworms can negatively impact the diversity and abundance of native plant species (Gundale 2002;Hale et al 2006;Nuzzo et al 2009;Hopfensperger et al 2011), though the magnitude of these effects may vary depending on site factors and the species of earthworm involved (Bohlen et al 2004c, Hale et al 2005bHale et al 2006;Holdsworth et al 2007).…”
Section: Introductionmentioning
confidence: 98%